Characterization and first‐in‐human clinical dose‐escalation safety evaluation of a next‐gen human freeze‐dried plasma. Issue 2 (24th December 2021) - Cancelas, Jose A.; Nestheide, Shawnagay; Rugg, Neeta; Eckerman, Anna; Macdonald, Victor W.; L. Charles, Matthew; Markstrom, Luke; Atkinson, Andrew J.; King, Melissa R.; Snyder, Michele; Burgess, David; Murto, James; et al.
Abstract: Background: Early plasma transfusion is life‐saving for bleeding trauma patients. Freeze‐dried plasma (FDP) provides unique formulation advantages for infusion in the prehospital setting. We describe characterization and clinical safety data of the first, next‐generation FDP stored in plastic bags with rapid reconstitution. Study design and methods: Coagulation and chemistry parameters on 155 pairs of fresh frozen plasma (FFP) and their derivative FDP units were compared. Next, a first‐in‐human, dose‐escalation safety evaluation of FDP, involving 24 healthy volunteers who donated either whole blood or apheresis plasma to create autologous FDP, was performed in three dose cohorts (270, 540, and 810 ml) and adverse events (AEs) were monitored. Cohort 3 was randomized, double‐blind with a cross‐over arm that compared FDP versus FFP using descriptive analysis for AEs, coagulation, hematology, and chemistry parameters. Results: FDP coagulation factors, clotting times, and product quality (pH, total protein, and osmolality) post‐lyophilization were preserved. FDP infusions, of up to 810 ml per subject, were found to be safe and with no serious AEs (SAEs) related to FDP. The average time to reconstitute FDP was 67 s (range: 43–106). No differences in coagulation parameters or thrombin activation were detected in subjects infused with 810 ml of FDP compared with FFP. Conclusion: This first next‐generation FDP product preserves the potency and safety of FFP in a novel rugged, compressible, plastic container, for rapid transfusion, allowing rapid access to plasma in resuscitation protocols for therapy in acute traumatic hemorrhage. Abstract : See editorial on page 257–260, in this issue